Polydimethylsiloxane (PDMS) microfluidic modifications for cell-based immunofluorescence assay. Issue 9 (3rd May 2021) - Khemthongcharoen, Numfon; Uawithya, Panapat; Chanasakulniyom, Mayuree; Yasawong, Montri; Jeamsaksiri, Wutthinan; Sripumkhai, Witsaroot; Pattamang, Pattaraluck; Juntasaro, Ekachai; Houngkamhang, Nongluck; Thienthong, Therdthai; Promptmas, Chamras
Abstract: Polydimethylsiloxane (PDMS) is a hydrophobic elastomer commonly used for microfluidic fabrication. PDMS has to be modified to improve its hydrophilicity and thus inhibits non-specific protein adsorption. This work evaluates the modification materials for the development of microfluidic cell-based immunofluorescence (IF) assay. In cell-based IF assay, PDMS is modified not just to inhibit the adsorption of non-specific florescent-conjugated protein that causes the elevation of background signal, but also to firmly support cell adhesion for subsequent immunostaining procedure. PDMS materials modified by three regular modification materials consisting of an extracellular matrix (poly-L-lysine; PLL), a hydrophilic polymer (polyvinyl alcohol; PVA) and a non- ionic surfactant (pluronic F127) were compared with each other based on hydrophilicity improvement, minimization of non-specific background signal, and enhancement of human embryonic kidney (HEK) cell adhesion. Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) analysis confirms that all modification materials are successfully immobilized on the PDMS surfaces. Due to its antifouling mechanism, pluronic modification greatly improves the hydrophilicity of the PDMS and inhibits non-specific protein adsorption. Even though the hydrophilicity and non-specific protein adsorption resistivity of the PDMS modified with PLL did not significantly differ from those of the unmodified PDMS, PLL modification obviously promotes HEK cell adhesion. Negative control and Myelin Oligodendrocyte Glycoprotein (MOG) expressing HEK cells were immobilized in microfluidics for IF assay evaluation. Results demonstrate that positive MOG expressing cells can be selectively stained by anti-MOG IgG antibody within 1 h at room temperature. Microfluidic platforms also enhance immobilized cell distribution, which compatibly supports single-cell analysis technique.